Four weekends and a funeral : a novel - Palmer, Ellie, 1989- (G. P. Putnam's Sons, 2024)
"A woman attends her ex-boyfriend's funeral only to discover that his family thinks they're still together, and her decision to play the grieving girlfriend all the while falling in love with his best friend"--